11.1: Invited Paper: Color theory and its application in laser display. (24th February 2021) - Wang, Guan; Gu, Chun; Xu, Lixin
Abstract : In this papers, we use the stereoscopic color gamut to analy the performance of the color gamut in the laser display systems. Optimal RGB value is proposed and calculated by the luminance of the three primary colors. We calculated the coverage of different light sources to NTSC, Rec.709, Rec.2020 color gamut standards by grid method.Through the white point balancing of the multi‐primary display system, we have calculated the stereoscopic color gamut of 4 and 6 primaries display system. we designed a color discrimination experiment for ordinary people and people with color vision deficits, results show that laser display can improve the color recognition ability of human eyes.